Study on capture power of the sealed-buoy wave energy converter in low energy flow density area. (June 2020) - Derong, Duan; Fei, Chen; Hui, Zhang; Xuefeng, Yang; Fang, Zhao
Abstract: In order to achieve the conversion of the wave energy into electrical energy in low energy flow density sea areas in this paper, the capture power of the sealed-buoy wave energy converter (SBWEC) was investigated by dynamics methods of rigid bodies based on the hydrology data of Shandong Peninsula. The effect of buoy diameter on the response amplitude operator (RAO) was studied using frequency domain analysis method. The effect of buoy diameter on the instantaneous capture power and the effect of mooring angle on the pitch time domain response were studied using time domain analysis method. Results show that the pitch RAO is increased by 10.5 times from 8°/m to 93°/m with the decrease in buoy diameter. The maximum pitch time domain response and capture power are obtained in the SBWEC with the diameter 15m, mooring angle 45° and the slider mass 40 Kg. It is derived that the average capture power and wave energy conversion efficiency are 44.1 KW and 54.44% for the SBWEC in low energy flow density sea areas. Then, the relevant research results provide some reference for the design and utilization of wave energy converter in low energy flow density sea areas. Graphical abstract: Image 1 Highlights: The SBWEC used in low energy flow density seas is studied. The optimal buoy diameter and mooring angle are 15m and 45°, respectively. The average capture power 44.1 KW is obtained in wave frequency range 0.24–0.48Hz. The optimal mass of the slider to obtain maximum efficiency is 40 Kg. The conversion efficiency reaches to 54.44% in low energy flow density seas.